The Development of Precision Agriculture Research in Modern Agriculture: A Bibliometric Study 2010–2024 - Loso Judijanto (West Science Agro, 2026)
Precision agriculture has emerged as a transformative approach in modern agriculture by integrating advanced technologies such as remote sensing, artificial intelligence, machine learning, Internet of Things (IoT), robotics, and big data analytics to improve agricultural productivity and sustainability. Given the rapid expansion of research in this field, a comprehensive understanding of its intellectual structure and development trends is essential. This study aims to analyze the evolution of precision agriculture research through a bibliometric examination of global scientific publications indexed in the Scopus database from 2010 to 2024. Bibliometric techniques were employed to evaluate publication trends, influential authors, institutions, countries, and highly cited literature. Furthermore, network visualization analyses using VOSviewer were conducted, including co-authorship, institutional collaboration, country collaboration, co-citation, keyword co-occurrence, overlay visualization, and density visualization. The findings reveal a significant increase in publication output over the study period, reflecting growing academic and practical interest in precision agriculture. India, China, the United States, and the Russian Federation emerged as the most influential contributors in terms of collaboration and research productivity. The most highly cited literature focused on nanotechnology, hyperspectral imaging, sustainable nutrient management, agricultural robotics, and smart farming technologies. Keyword analysis identified precision agriculture, sustainable development, smart agriculture, crops, Internet of Things, machine learning, and artificial intelligence as dominant research themes. Overlay visualization further demonstrated a transition from traditional topics such as soil fertility and crop management toward digitally enabled and sustainability-oriented agricultural systems. The results indicate that precision agriculture has evolved into a highly interdisciplinary field that combines technological innovation and sustainable development principles to address global agricultural challenges. The study provides valuable insights into current research trends and future directions for researchers, policymakers, and practitioners engaged in modern agricultural development.